2012
DOI: 10.1177/0044118x12443372
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Youth Engagement in HIV-Preventive Structural Change Interventions

Abstract: Youth are infrequently included in planning the health promotion projects designed to benefit them as many of the factors infringing upon youth’s health and well-being also limit their engagement in community-based public health promotion projects. This article explores youth engagement in 13 coalitions implementing structural changes meant to reduce HIV transmission among adolescents. There was wide variation of youth membership and involvement across coalitions. Using analytic induction, the authors show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 33 publications
(60 reference statements)
1
28
0
Order By: Relevance
“…Few of the adolescent medicine trials units are steeped in a culture of or experienced at engaging youth in the clinical work and medical research which constitutes their staff’s greatest expertise. Youth involvement varied substantially as a consequence (Reed and Miller 2014). Though most tried to engage youth, all but a few coalitions struggled to engage youth in meaningful roles over their initial 4 years (Reed and Miller 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few of the adolescent medicine trials units are steeped in a culture of or experienced at engaging youth in the clinical work and medical research which constitutes their staff’s greatest expertise. Youth involvement varied substantially as a consequence (Reed and Miller 2014). Though most tried to engage youth, all but a few coalitions struggled to engage youth in meaningful roles over their initial 4 years (Reed and Miller 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Youth involvement varied substantially as a consequence (Reed and Miller 2014). Though most tried to engage youth, all but a few coalitions struggled to engage youth in meaningful roles over their initial 4 years (Reed and Miller 2014). …”
Section: Methodsmentioning
confidence: 99%
“…In a community-based participatory research project on health promotion involving homeless youth, for example, Garcia, Minkler, Cardenas, Grills, and Porter (2014) described the success of youth researchers in changing policy (e.g., related to recreation). Further, youth engagement in programs intended to reduce HIV transmission among youth found that greater, more meaningful youth engagement was linked to more success in program objectives (Reed & Miller, 2014). Reed and Miller (2014) also identified the successful functioning of the projects as, in themselves, tangible contributions, as their existence changes the structure of a system that has not been inviting to youth participation.…”
Section: The Process Of Y-apsmentioning
confidence: 99%
“…Further, youth engagement in programs intended to reduce HIV transmission among youth found that greater, more meaningful youth engagement was linked to more success in program objectives (Reed & Miller, 2014). Reed and Miller (2014) also identified the successful functioning of the projects as, in themselves, tangible contributions, as their existence changes the structure of a system that has not been inviting to youth participation.…”
Section: The Process Of Y-apsmentioning
confidence: 99%
See 1 more Smart Citation